PENDAMPINGAN PENGOLAHAN PERMEN JELLY NANAS UNTUK PENGUATAN EKONOMI MASYARAKAT DESA PAGARUYUNG PROVINSI RIAU - Yusmarini; Dewi Fortuna Ayu; Riftyan, Emma; Yossie Kharisma Dewi; Nur Hasnah AR; Yusni Maulida; Siswanto (LPPM ITB AAS Indonesia Surakarta, 2024)
Pagaruyung Village is the largest producer of pineapples in Kampar District, with sales reaching 10,330 tons annually. Farmers sell high-quality fresh pineapple but at a low market price of around IDR 3,000-5,000 per fruit. Making processed products from pineapple fruit, such as pineapple jelly candy, can effectively overcome the problem, creating a distinctive Village identity that is attractive to tourists and supports food security independently. The mission of the community service program through the assistance of Pagaruyung Village, Tapung District, is to transform Pagaruyung Village into an entrepreneurial Village to create a self-sufficient Village and improve the economy of the Village community through synergy between Riau University as a university and assist villages within the scope of Riau Province. In this activity, the approach was carried out through the socialization of pineapple processed products, making pineapple jelly candy with simple technology, and evaluating activities using questionnaires. The impact of this training shows that the community has a strong desire and enthusiasm for creating pineapple jelly candy from pineapple fruit. Continuous coaching and training efforts are needed to achieve the main goal, which is to improve the local economy and make Pagaruyung Village a tourist destination.